(untitled) (Revista de Ciências Agroveterinárias, 2020)
Maize is highly demanding and responsive to nitrogen (N) fertilization, inserted in several production systems, with the recent highlight for integrated production systems. This study aimed to assess the effect of N rates on maize, as well as the economic aspect in an integrated production system. The experimental design was a randomized complete block design with four replicates. Four N rates in topdressing (0, 40, 80, and 120 kg ha-1) were assessed. Maize was cultivated under black oat and ryegrass mixed straw. Stem diameter, main ear insertion height, and ear parameters, except for the number of rows per ear, which increased linearly as a function of N rates, in turn, plant height responded quadratically until 81 kg N ha-1. Grain yield increased significantly as a function of N, indicating a residual effect of winter fertilization and high N use efficiency in the production system. The highest grain yield and profitability were obtained at the rate of 120 kg N ha-1.